Dosing related effects of zoledronic acid on bone markers and creatinine clearance in patients with multiple myeloma and metastatic breast cancer. (April 2014) - Søe, Kent; Delaissé, Jean-Marie; Jakobsen, Erik H.; Hansen, Charlotte T.; Plesner, Torben
Abstract Zoledronic acid (Zol) is frequently used for the treatment of bone disease in patients with multiple myeloma and breast cancer with metastasis to bone. Therefore, there is also an interest in finding the optimal dosing regimen to optimize effects, minimize side effects and reduce costs. In our phase II clinical trial we investigated the effect of Zol treatment on the serum levels of the bone markers collagen type 1 cross-linked C-telopeptide (CTX) and bone specific alkaline phosphatase (bALP) as well as on creatinine clearance (kidney function) in response to dosing and duration of treatment for each individual patient. Methods. We enrolled 30 multiple myeloma (MM) and 30 breast cancer (BC) patients whereof 10 of each had never received bisphosphonate and 20 had received at least six prior Zol treatments. Results. We found that Zol treatment strongly reduced CTX (Spearman's correlation, rs = −0.59, p = 0.0007) and bALP (Spearman's correlation, rs = −0.51, p = 0.0042) in MM patients while only CTX (Spearman's correlation, rs = −0.42, p = 0.024) was significantly affected in BC patients. Multiple linear regression analyses done on the entire cohort showed that the average time between each dose of Zol had the strongest impact on CTX (p < 0.001) and bALP (p = 0.011) levels while the total accumulated number of Zol infusions had a less pronounced effect on CTX levels (p = 0.015). In contrast, multiple linear regression analysis showed that the total number of Zol infusions had a strong negative impact on kidney function (p = 0.014) while the average time between each dose of Zol had no significant impact. Conclusion. Thus, if MM and BC patients are not treated regularly every month with Zol bone turnover is not fully suppressed, while prolonged treatment with zoledronic acid compromises kidney function. We believe that these data significantly contribute to the knowledge needed to find the optimal Zol treatment schedule.